Determinants of Customer Satisfaction on Retail Banking in Nepal - Timalsina, Dhanishor (Bhairahawa Campus Journal, 2024)
Customer satisfaction is paramount for bank success and customer retention. The study in Rupandehi District's commercial banks aimed to identify key determinants of customer satisfaction. Analyzing the reliability, assurance, responsiveness, empathy, and tangible as independent variables, the study found that reliability, assurance, and tangibles significantly impact customer satisfaction positively. However, empathy and responsiveness had negligible effects. 180 samples were selected from the Rupandehi District, and a structured survey questionnaire was distributed to all the samples. The responses of all 180 samples have been collected, but 30 responses have outlier problems, so only 150 have been analyzed. The findings emphasize the need for banks to prioritize reliability, assurance, and tangible aspects of service delivery to enhance customer satisfaction, ensuring a sustainable competitive advantage in the long term.